2013
DOI: 10.1242/dev.091744
|View full text |Cite
|
Sign up to set email alerts
|

Cdks, cyclins and CKIs: roles beyond cell cycle regulation

Abstract: SummaryCyclin-dependent kinases (Cdks) are serine/threonine kinases and their catalytic activities are modulated by interactions with cyclins and Cdk inhibitors (CKIs). Close cooperation between this trio is necessary for ensuring orderly progression through the cell cycle. In addition to their well-established function in cell cycle control, it is becoming increasingly apparent that mammalian Cdks, cyclins and CKIs play indispensable roles in processes such as transcription, epigenetic regulation, metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
1,088
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,281 publications
(1,126 citation statements)
references
References 137 publications
25
1,088
0
13
Order By: Relevance
“…Consequently, they may fulfill different functions than their known contribution to the cell cycle progress. 21,22 Polyploidy of some neurons has also been viewed as supporting the cell cycle-related neuronal death hypothesis, but physiologic neuronal polyploidy has been described. 23 In the present study, we demonstrated that S phase markers cyclin A, cdk2 and PCNA were expressed in the nuclei of neurons in brain areas were FPV proteins were produced in the cytoplasm and accumulated in the nuclei of neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they may fulfill different functions than their known contribution to the cell cycle progress. 21,22 Polyploidy of some neurons has also been viewed as supporting the cell cycle-related neuronal death hypothesis, but physiologic neuronal polyploidy has been described. 23 In the present study, we demonstrated that S phase markers cyclin A, cdk2 and PCNA were expressed in the nuclei of neurons in brain areas were FPV proteins were produced in the cytoplasm and accumulated in the nuclei of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…13 Over the last 2 decades, neuronal cell cycle re-entry, as a possible common bottle neck for most nervous system degenerative processes, has been subjected to intensive researches and controversies. [14][15][16][17][18][19][20][21][22][23] To our knowledge, this study is the first one demonstrating the existence of neuronal nuclei expressing S phase markers in the frame of a spontaneously occurring infectious disease and represents an example of inflammatory/ infectious link to the neuronal cell cycle reentry phenomenon.…”
Section: Introductionmentioning
confidence: 96%
“…It is well established that E-type cyclins interact with the kinase CDK2 and D-type cyclins form a complex with the kinases CDK4 or CDK6 during cell proliferation. 18,19 These cyclin-CDK complexes phosphorylate retinoblastoma (Rb) protein family members, leading to E2F release from Rb and regulation of cell cycle progression from the G 1 phase into the S phase. 20 Therefore, cyclin E, cyclin D, and their related CDKs have important roles in cell proliferation.…”
Section: Low Doses Of I3c Inhibit Proliferation Of Cancer Cells By Sementioning
confidence: 99%
“…1,2 CDKs (CDK1-CDK6) mostly promote the progression from one cell-cycle phase to the next, and CDK1 is essential for proliferation. CDKs have been characterized extensively, and some of their substrates and in vivo functions are known.…”
Section: Introductionmentioning
confidence: 99%
“…CDKs have been characterized extensively, and some of their substrates and in vivo functions are known. 1,3 Another group of CDKs, e.g., CDK7-CDK9 and CDK11-CDK13, are mostly involved in transcription. Most of the remaining CDKs are ''orphan'' kinases, which have been poorly studied.…”
Section: Introductionmentioning
confidence: 99%